The Native Microbial Community of Gastropod-Associated Phasmarhabditis Species Across Central and Southern California - Schurkman, Jacob; Liu, Rui; Alavi, Salma; Tandingan De Ley, Irma; Hsiao, Ansel; Dillman, Adler R. (Frontiers in Microbiology, 2022)
Nematodes in the genus Phasmarhabditis can infect and kill slugs and snails, which are important agricultural pests. This useful trait has been commercialized by the corporation BASF after they mass produced a product labeled Nemaslug®. The product contains Phasmarhabditis hermaphrodita which has been cultured with Moraxella osloensis, a bacterial strain that was originally thought to be responsible for causing mortality in slugs and snails. The exact mechanism leading to death in a Phasmarhabditis infected host is unknown but may involve contributions from nematode-associated bacteria. The naturally occurring microbial community of Phasmarhabditis is unexplored; previous Phasmarhabditis microbial community studies have focused on lab grown or commercially reared nematodes, and in order to obtain a deeper understanding of the parasite and its host interactions, it is crucial to characterize the natural microbial communities associated with this organism in the wild. We sampled Phasmarhabditis californica, Phasmarhabditis hermaphrodita, and Phasmarhabditis papillosa directly from their habitats in Central and Southern California nurseries and garden centers and identified their native microbial community via 16S amplicon sequencing. We found that the Phasmarhabditis microbial community was influenced by species, location, and possibly gastropod host from which the nematode was collected. The predominant bacteria of the Phasmarhabditis isolates collected included Shewanella, Clostridium perfringens, Aeromonadaceae, Pseudomanadaceae, and Acinetobacter. Phasmarhabditis papillosa isolates exhibited an enrichment with species belonging to Acinetobacter or Pseudomonadaceae. However, further research must be performed to determine if this is due to the location of isolate collection or a species-specific microbial community pattern. More work on the natural microbial community of Phasmarhabditis is needed to determine the role of bacteria in nematode virulence.